Emerging horizons: clinical applications and multifaceted benefits of SGLT-2 inhibitors beyond diabetes - Feng, Qing; Wu, Miaoqiong; Mai, Zizhao (Frontiers in Cardiovascular Medicine, 2025)
SGLT-2 inhibitors, initially developed for type 2 diabetes, demonstrate profound cardiorenal and metabolic benefits. This review synthesizes evidence from clinical trials and mechanistic studies to elucidate their roles in cardiovascular diseases, chronic kidney disease, and non-alcoholic fatty liver disease. Key findings include a notable reduction in cardiovascular death/heart failure hospitalization, a marked decrease in heart failure hospitalization risk, and significant improvements in renal and hepatic outcomes. Emerging mechanisms, such as autophagy induction, ketone utilization, and anti-inflammatory effects, underpin these benefits. Ongoing trials explore their potential in non-diabetic populations, positioning SGLT-2 inhibitors as transformative agents in multisystem disease management.